124. Activity of Novel b-Lactam/b-Lactamase Inhibitor (BL/BLI) Combinations Against AmpC-Producing Species Collected in United States Hospitals. (15th December 2022) - Castanheira, Mariana; Streit, Jennifer M; Carvalhaes, Cecilia G; Mendes, Rodrigo E; Shortridge, Dee
Abstract: Background: Therapeutic options for Enterobacterales species known to overexpress chromosomal AmpC (AmpC producers) are limited since these organisms can develop resistance to BLs during therapy. Novel BL/BLIs, such as meropenem-vaborbactam (MEV), ceftazidime-avibactam (CZA), and imipenem-relebactam (IMR), display activity against isolates producing serine-carbapenemases, extended-spectrum β-lactamases, and AmpC enzymes. In this study, we evaluated the activity of novel BL/BLIs against a collection of AmpC producers collected in from US hospitals during 2021. Activity of newer BL/BLI combinations against AmpC producers Methods: A total of 1, 252 AmpC producers including were consecutively collected in 31 US hospitals. Isolates were susceptibility tested by reference broth microdilution methods. CLSI breakpoints were applied. Results: The activity of new BL/BLIs is summarized displayed in the Figure. MEV (MIC50/90, 0.03/0.06 mg/L) and amikacin were the most active agents tested against these isolates, inhibiting 99.8%. CZA (MIC50/90, 0.12/0.5 mg/L) inhibited 99.5%. IMR (MIC50/90, 0.12/1 mg/L) was active against 95.9%. Cefepime and meropenem were active against 92.0% and 97.6% of these isolates, respectively. Piperacillin-tazobactam and ceftolozane-tazobactam (MIC50/90, 0.5/8 mg/L) displayed activity against 76.4% and 83.6% of the AmpC producers, respectively. Tigecycline was active against 96.8% of the isolates; only 53.8% of the isolates had a colistin MIC of ≤2 mg/L. A total of 39 (3.2%) AmpC producers were nonsusceptible to imipenem and/or meropenem. MEV (MIC50/90, 0.25/2 mg/L) was active against 92.3%. IRL (MIC50/90, 0.25/2 mg/L) and CZA (MIC50/90, 1/ > 32 mg/L) were active against 89.7% of the carbapenem nonsusceptible AmpC producers. Against cefepime-resistant AmpC producers ( n =45; 3.6%), MEV, IMR, and CZA had 93.3%, 88.9%, and 86.7% activity. Conclusion: Infections caused by AmpC producers often are challenging to treat. Understanding the activity of new BL/BLIs is important as the use of cefepime and meropenem can also lead to resistance to these agents. MEV, IRL, and CZA displayed good activity against AmpC producers. When analyzing carbapenem-nonsusceptible or cefepime-resistant isolates, MEV was slightly more active but more potent than other BL/BLI combinations. Disclosures: Mariana Castanheira, PhD, AbbVie: Grant/Research Support|Cidara: Grant/Research Support|GSK: Grant/Research Support|Melinta: Grant/Research Support|Pfizer: Grant/Research Support|Shionogi: Grant/Research Support Jennifer M. Streit, BS, MT(ASCP), Cidara: Grant/Research Support|GSK: Grant/Research Support|Melinta: Grant/Research Support|Shionogi: Grant/Research Support Cecilia G. Carvalhaes, MD, PhD, AbbVie: Grant/Research Support|Cidara: Grant/Research Support|Melinta: Grant/Research Support|Pfizer: Grant/Research Support Rodrigo E. Mendes, PhD, AbbVie: Grant/Research Support|Cidara: Grant/Research Support|GSK: Grant/Research Support|Melinta: Grant/Research Support|Nabriva Therapeutics: Grant/Research Support|Office for Assistant Secretary of Defense for Health Affairs: Grant/Research Support|Pfizer: Grant/Research Support|Shionogi: Grant/Research Support|Spero Therapeutics: Grant/Research Support Dee Shortridge, PhD, AbbVie: Grant/Research Support|JMI Laboratory: Employee|Melinta: Grant/Research Support|Menarini: Grant/Research Support|Shionogi: Grant/Research Support.